Practices of Complementary Feeding of Mothers Attending a Tertiary Care Teaching Hospital in the Northern Part of Bangladesh (TAJ: Journal of Teachers Association, 2022)
Background: Adequate nutrition during infancy and early childhood are essential to ensure growth and development, and it depends significantly on the pattern of complementary feeding. As Bangladesh is a high burden of infant malnutrition, the present study was designed to assess the practices regarding complementary feeding among mothers attending a tertiary care hospital.  Objective: To observe the attitude and practices of mothers regarding complementary feeding.  Methodology: This cross-sectional study was conducted at the Department of Pediatrics in Rajshahi Medical Hospital for one year. A total of 227 mothers of children aged between 6 to 24 months attending pediatric OPD at Rajshahi Medical Hospital were included in this study. Data collection was conducted through a pre-designed questionnaire. After data collection of data, data were analyzed by SPSS 23.0.Results: A total of 227 parents were interviewed. The mean age of the respondents was 26±8.42 (SD) years. Nearly half (45%) of the mothers belonged to lower-middle-income families. Of all, 82% of the mothers knew about the perception of complementary feeding, and about 21% knew the WHO recommended age for complimentary food initiation (at six months). About 71% and 60% had knowledge about iron-rich food and iodized salt accordingly. Half of them knew the appropriate consistency of complimentary food. About 64% of mothers gave complementary foods ≤2 times a day while 36% fed≥3 times a day. Regarding attitude, 78% of mothers approached the necessity of maintaining dietary diversity and variety of food for a balanced diet. In comparison, 52% preferred homemade food, 22% preferred commercially available food, and 26% preferred a combination of both. About 71.8% of mothers believed in different food taboos. In this study, dilution of cow's milk as a complementary food was done by 76% of mothers, while complementary feeding was discontinued by 80%. About 78% and 65% of the mothers reported washing their hands and utensils and baby's hand before feeding the child, 66% of them covered the food after cooking, and 43% reheated the food before serving.Conclusion: This study shed light on existing knowledge, attitude, and practice among mothers attending a tertiary care hospital. But to get the exact scenario, further extensive study is recommended.TAJ 2022; 35: No-1: 83-90